2013
DOI: 10.1016/j.bbr.2012.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of striatal adenosine A2A receptor spares latent inhibition and prepulse inhibition but impairs active avoidance learning

Abstract: Following early clinical leads, the adenosine A2AR receptor (A2AR) has continued to attract attention as a potential novel target for treating schizophrenia; especially against the negative and cognitive symptoms of the disease because of A2AR’s unique modulatory action over glutamatergic in addition to dopaminergic signaling. Through the antagonistic interaction with the dopamine D2 receptor, and by regulating glutamate release and N-methyl-d-aspartate receptor function, striatal A2AR is ideally positioned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…D2R antagonism, including in the CeA specifically, has been demonstrated to decrease two-way avoid-escape and increase fear (Perez de la Mora et al, 2010;Reis et al, 2004). The D2R interacts antagonistically with the adenosine receptor A2AR by forming heteromers (Boison et al, 2012); because expression of both Drd2 and Adora2a was decreased by CSD it is difficult to predict the functional consequences; nonetheless it is noteworthy that striatum-specific Adora2a knockout mice exhibited decreased activity and two-way avoid-escape (Singer et al, 2013), as observed in CSD mice. Both Adora2a and Gpr88 exhibit enriched expression in the central extended AMYG and dorsal striatum (Becker et al, 2008); accordingly, the decreased expression observed in CSD mice might have occurred primarily in CeA indicating that future studies should analyse CSD effects on gene expression here and in striatal regions.…”
Section: Discussionmentioning
confidence: 99%
“…D2R antagonism, including in the CeA specifically, has been demonstrated to decrease two-way avoid-escape and increase fear (Perez de la Mora et al, 2010;Reis et al, 2004). The D2R interacts antagonistically with the adenosine receptor A2AR by forming heteromers (Boison et al, 2012); because expression of both Drd2 and Adora2a was decreased by CSD it is difficult to predict the functional consequences; nonetheless it is noteworthy that striatum-specific Adora2a knockout mice exhibited decreased activity and two-way avoid-escape (Singer et al, 2013), as observed in CSD mice. Both Adora2a and Gpr88 exhibit enriched expression in the central extended AMYG and dorsal striatum (Becker et al, 2008); accordingly, the decreased expression observed in CSD mice might have occurred primarily in CeA indicating that future studies should analyse CSD effects on gene expression here and in striatal regions.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have found that agonists impair memory retrieval in rats (Pereira et al, 2005), others show cognitive enhancement in A 2A R KO mice (Shen et al, 2012) or after treatment with specific A 2A R antagonists (Takahashi, 2008), and some suggest that the activation of adenosine A 2A R is sufficient to induce cognitive impairments in mice (Pagnussat et al, 2015). On the contrary, other studies have shown alterations in the active avoidance paradigm in striatum-specific A 2A R KO mice (Singer et al, 2013), and the deletion of adenosine A 2A R induced changes in episodic memory assessed with the novel object recognition test . The selective inactivation of A 2A R in astrocytes also impairs working memory in mice (Matos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Given the prominent role of the DMS in control of goal-directed behavior, our finding that focal knockdown of striatopallidal A 2A Rs in DMS captures the goal-directed characteristics of striatum-specific A 2A R knockout mice argue that striatum-A 2A R KO mice displayed enhanced goal-directed behavior, but manifested as impaired habit formation (Yu et al, 2009 (Mingote et al, 2008;Nunes et al, 2013 (Tai et al, 2012), and that loss of striatal long-term depression (LTD) largely restricted to striatopallidal neurons is associated with a shift in behavioral control from goal-directed action to habitual responding (Nazzaro et al, 2012). Together with increasing evidences from diverse learning paradigms that striatopallidal A 2A Rs assume an inhibitory control over working memory (Wei et al, 2011;Zhou et al, 2009), fear condition (Singer et al, 2013;Wei et al, 2014), reversal learning (Wei et al, 2011) and instrumental learning (Yu et al, 2009), we postulate that postsynaptic striatopallidal A 2A R function may provide a "break" mechanism to constrain some cognitions including instrumental learning (Chen, 2014 Mice were under CRF training followed by RI30 and then RI60 training with or without optoA 2A R stimulation as described in the Methods. The performances of optoA 2A R mice with "time-locked" stimulation (n=13) or with "light off" (n=10) during the acquisition phase were indistinguishable (repeated-measures ANOVA, RI training course X optogenetic stimulation interaction; F 5,105 =0.916, P>0.05; optoA 2A R stimulation main effect; F 1,21 =0.156, p>0.05).…”
Section: The Striatopallidal a 2a R Signaling In The Dms Provides A "mentioning
confidence: 93%